Prognostic Factors for Survival and Relapse in ANCA-Associated Vasculitis with Renal Involvement: A Clinical Long-Term Follow-Up Study - Anna Salmela; Tom Törnroth; Tuija Poussa; Agneta Ekstrand (International Journal of Nephrology)
Aim. We describe the clinical pattern of ANCA-associated vasculitis (AAV) and assess long-term prognostic factors of patients and renal survival and relapse. Methods. Data from 85 patients with renal biopsy-proven AAV at a single center with up to 20-year [median 16.2 years (95% CI 14.9-17.7)] follow-up were retrospectively collected. Results. Overall, 55% of the patients had microscopic polyangiitis (MPA) and 45% had granulomatosis with polyangiitis (GPA). The histopathological classes were focal in 35%, crescentic in 26%, mixed in 20%, and sclerotic glomerulonephritis in 19% of the patients. As induction treatment, a combination of cyclophosphamide and corticosteroids was given to 82%, while a combination of azathioprine and corticosteroids was maintenance therapy in 79%. The twenty-year patient survival was 45%. In a multivariable analysis, age ≥58 years [hazard ratio (HR) 7.64, 95% CI 3.44-16.95] and myeloperoxidase (MPO) ANCA (HR 2.12, 95% CI 1.08-4.17) were associated with shorter patient survival time. Renal survival was 68% overall: 88% in focal, 71% in crescentic, 56% in mixed, and 37% in sclerotic class (p=0.01). Female sex (HR 0.26, 95% CI 0.10-0.73) was a predictor of improved renal survival, whereas GFR <30 ml/min and MPO-ANCA were associated with worse renal survival (HR 4.10, 95% CI 1.35-12.49 and HR 3.10, 95% CI 1.21-7.95, respectively). Relapse-free survival at 20 years was 10%. MPA was associated with a lower risk for relapse (HR 0.48, 95% CI 0.28–0.82). Conclusion. We confirmed the improved patient and renal survival in AAV patients with glomerulonephritis, while relapse remained the primary challenge. Histopathological classification may be relevant for survival.